Consumer attitudes, motivations and barriers towards sheep and goat dairy products - Mandolesi, Serena; Naspetti, Simona; Arsenos, Georgios; Caramelle-Holtz, Emmanuelle; Latvala, Terhi; Martin-Collado, Daniel; Orsini, Stefano; Ozturk, Emel; Zanoli, Raffaele (Elsevier, 2024)
Sheep and goat dairy products are part of the culinary tradition of most European countries. The paper explores consumers' perceptions and attitudes towards sheep and goat dairy products within seven European countries. A combination of focus group discussions and laddering interviews were used. Results showed that most consumers perceived those products as a speciality food with a unique taste that can be perceived as good or bad. Perceived quality, naturality and healthiness are the dominant motivational structures, while value-for-money is a secondary concern. More focus on communicating the hedonic dimension and positive health-related messages may increase consumers’ interest and acceptance.
Keywords: goal-oriented behaviour; consumer research; food consumption; means-end chain theory